Moonlighting Proteins Are Important Players in Cancer Immunology - Adamo, Annalisa; Frusteri, Cristina; Pallotta, Maria Teresa; Pirali, Tracey; Sartoris, Silvia; Ugel, Stefano (Frontiers in Immunology, 2021)
Plasticity and adaptation to environmental stress are the main features that tumor and immune system share. Except for intrinsic and high-defined properties, cancer and immune cells need to overcome the opponent's defences by activating more effective signaling networks, based on common elements such as transcriptional factors, protein-based complexes and receptors. Interestingly, growing evidence point to an increasing number of proteins capable of performing diverse and unpredictable functions. These multifunctional proteins are defined as moonlighting proteins. During cancer progression, several moonlighting proteins are involved in promoting an immunosuppressive microenvironment by reprogramming immune cells to support tumor growth and metastatic spread. Conversely, other moonlighting proteins support tumor antigen presentation and lymphocytes activation, leading to several anti-cancer immunological responses. In this light, moonlighting proteins could be used as promising new potential targets for improving current cancer therapies. In this review, we describe in details twelve unprecedented moonlighting proteins that during cancer progression play a decisive role in guiding cancer-associated immunomodulation by shaping innate or adaptive immune response.